A QoE centric distributed caching approach for vehicular video streaming in cellular networks. Issue 12 (18th September 2015) - Sun, Fei; Liu, Bo; Hou, Fen; Zhou, Haibo; Chen, Jiacheng; Rui, Yun; Gui, Lin
Abstract: Distributed caching‐empowered wireless networks can greatly improve the efficiency of data storage and transmission and thereby the users' quality of experience (QoE). However, how this technology can alleviate the network access pressure while ensuring the consistency of content delivery is still an open question, especially in the case where the users are in fast motion. Therefore, in this paper, we investigate the caching issue emerging from a forthcoming scenario where vehicular video streaming is performed under cellular networks. Specifically, a QoE centric distributed caching approach is proposed to fulfill as many users' requests as possible, considering the limited caching space of base stations and basic user experience guarantee. Firstly, a QoE evaluation model is established using verified empirical data. Also, the mathematic relationship between the streaming bit rate and actual storage space is developed. Then, the distributed caching management for vehicular video streaming is formulated as a constrained optimization problem and solved with the generalized–reduced gradient method. Simulation results indicate that our approach can improve the users' satisfaction ratio by up to 40 % . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, we propose a quality of experience centric distributed caching management approach considering the cache constraint of cellular networks, to fulfill more mobile users' requests for video streaming while ensuring the basic service experience of users.